2021
DOI: 10.2217/fca-2021-0011
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Prevention and Therapy in Women With Type 2 Diabetes

Abstract: Cardiovascular disease (CVD) is the leading cause of death among men and women, although women are usually underdiagnosed and experience a delay in diagnosis. This also occurs in women with type 2 diabetes mellitus, despite the fact that diabetes is recognized as a major cardiovascular risk factor. Several factors influence the gap between diagnosis and treatment of cardiovascular disease in women: lack of perception of cardiovascular risk, effects of sex-related risk factors and the action of drugs in women. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…Studies in mouse models have also shown the involvement of Lonp1 in atherosclerosis [ 69 ], and its oxidative inactivation after transaortic constriction (TAC) in mouse heart [ 70 ]. Atherosclerosis is a chronic inflammatory and metabolic disease and a major risk factor for myocardial infarction [ 71 , 72 ]. During atherosclerosis, Lonp1 is upregulated in macrophages by saturated fatty acids and by PERK-eIF2α activated signaling.…”
Section: The Role Of Lonp1 In Heart Homeostasis and Response To Stressmentioning
confidence: 99%
“…Studies in mouse models have also shown the involvement of Lonp1 in atherosclerosis [ 69 ], and its oxidative inactivation after transaortic constriction (TAC) in mouse heart [ 70 ]. Atherosclerosis is a chronic inflammatory and metabolic disease and a major risk factor for myocardial infarction [ 71 , 72 ]. During atherosclerosis, Lonp1 is upregulated in macrophages by saturated fatty acids and by PERK-eIF2α activated signaling.…”
Section: The Role Of Lonp1 In Heart Homeostasis and Response To Stressmentioning
confidence: 99%
“…22 The physiology of subcutaneous and visceral adipose in women is different compared to men, with over 2800 genes differentially expressed. 23 Men have larger fat cell sizes in the intra-abdominal compartment, whereas women have larger fat cell sizes in subcutaneous depots. 24 These sex differences in adiposity distribution influence the flux of fatty acids that occurs in fasting and feeding.…”
Section: Obesity and Womenmentioning
confidence: 99%
“…The gap in the diagnosis and treatment of cardiovascular disease in women depends on several factors: the lack of self-perception of cardiovascular risk, the exposure to risk factors that act with a difference in women and men, and specific sex-related risk factors, which are still little known. 41 …”
Section: Primary Prevention Of Cardiovascular Diseasementioning
confidence: 99%
“…40 The gap in the diagnosis and treatment of cardiovascular disease in women depends on several factors: the lack of self-perception of cardiovascular risk, the exposure to risk factors that act with a difference in women and men, and specific sex-related risk factors, which are still little known. 41 Sexual dimorphism in fat distribution and metabolism of adipose tissue and skeletal muscle affects sex differences in tissue-specific insulin sensitivity and cardiometabolic health. Additionally, sex hormones, such as estrogen and testosterone, as well as the complement of sex chromosomes, are likely to play a role in sex differences in cardiovascular disease.…”
mentioning
confidence: 99%